The Effectiveness of Logotherapy on Improving the Quality of Life of the Elderly: An Islamic Psychology Perspective - Aisyah, Lilis; Wangi, Eneng Nurlaili; Fahmi, Irfan (Faculty of Psychology, UIN Sunan Gunung Djati, Bandung Indonesia, 2025)
This study aims to examine the effectiveness of logotherapy in improving the quality of life of the elderly from the perspective of Islamic psychology. Logotherapy, which focuses on the search for life’s meaning, was applied to six elderly individuals at a care home in Tasikmalaya Regency. The method used was an experimental design with a one-group pretest-posttest approach, using the WHOQOL-BREF instrument to measure quality of life across physical, psychological, social, and environmental domains. The results showed a significant improvement (.027) with an average increase of 9.75%, particularly in the psychological domain (14.62%). These findings indicate that logotherapy helps elderly individuals find meaning in life and enhances their emotional and social well-being. From an Islamic perspective, the results align with the values of spirituality, patience (sabr), and trust in God (tawakkul). Islam also emphasizes the importance of a supportive environment, in line with the concept of khalifah, where humans are responsible for creating dignified living conditions, including for the elderly. Recommendations include sustained implementation of logotherapy and improved care home facilities.